Local Governance in the Midst of Economic Dependency: A Case Study of Olongapo City - J.M. Ian S. Salas (Philippine Institute for Development Studies (PIDS), 2004)
The experience of Olongapo City in managing economic distress due to the loss of its economic anchor, the Subic Bay Naval Base, offers a rich lesson in local governance on how critical it is to plan ahead. The risk of a severe downturn, primarily due to economic dependency, can be successfully shunned if the groundwork for recovery is immediately put in place. While population movements may exacerbate the situation and imperil finances, it is still possible to maintain a high quality of service delivery given the correct priorities.
Keywords: 330; economics enterprise development; population management; local government; economic dependency; Olongapo City; Subic Bay Naval Base; Subic Bay freeport; feminization of migration; revenue generation